You Reap What You Know: Darwin beats Malthus: Medicalization, Evolutionary Anthropology and the Demographic Transition - Katharina Mühlhoff (European Historical Economics Society (EHES), 2016)
For the better part of human history, life was most fragile and death most imminent during infancy and early childhood. The death of a child may be hardly bearable from a humanitarian perspective. Yet, certain currents in economic theory attach a silver lining to high mortality by claiming that the Malthusian check on population raises per capita income and facilitates the accumulation of capital. The present paper challenges this conventional wisdom. In essence, it argues that high levels of environmental risk produce genetic and behavioral adaptations which induce individuals to have many - in terms of parental investment - cheap offspring. Conversely, stable environments recast the tradeoff between child quantity and quality in favor of more quality-based reproductive strategies. Incorporating these biological relationships into the traditional Barro-Becker model of fertility, the paper finds that both declining extrinsic mortality and increased effectiveness of parenting effort potentially trigger a demographic transition. Thus, the economic benefits of Malthusian population checks are mitigated because high mortality endogenously produces high fertility whereas improved survival encourages human capital investment and fosters long-term growth. To assess whether the theoretical predictions conform with historical reality, I use smallpox vaccination in 19th century Germany as a natural experiment. Performing an econometric analysis of 67 districts in the Granduchy of Baden provides evidence, that comprehensive immunization and advanced medicalization came along with reduced mortality, significantly lower fertility and increased parental care. In sum, it therefore seems that Malthusian mechanisms are at least partly offset by countervailing biological adaptations.
Keywords: I12; I15; N13; N33; O44; 330; Demographic Transition; Evolutionary Anthropology; Life History Theory; Economic Growth